Integrative Approach to Phlebotomus mascittii Grassi, 1908: First Record in Vienna with New Morphological and Molecular Insights - Edwin Kniha; Vít Dvořák; Petr Halada; Markus Milchram; Adelheid G. Obwaller; Katrin Kuhls; Susanne Schlegel; Martina Köhsler; Wolfgang Poeppl; Karin Bakran-Lebl; Hans-Peter Fuehrer; Věra Volfová; et al. (Pathogens, 2020)
Sand flies (Diptera: Psychodidae: Phlebotominae) are blood-feeding insects that transmit the protozoan parasites Leishmania spp. and various arthropod-borne (arbo) viruses. While in Mediterranean parts of Europe the sand fly fauna is diverse, in Central European countries including Austria mainly Phlebotomus mascittii is found, an assumed but unproven vector of Leishmania infantum. To update the currently understudied sand fly distribution in Austria, a sand fly survey was performed and other entomological catches were screened for sand flies. Seven new trapping locations of Ph. mascittii are reported including the first record in Vienna, representing also one of the first findings of this species in a city. Morphological identification, supported by fluorescence microscopy, was confirmed by two molecular approaches, including sequencing and matrix-assisted laser desorption/ionization-time of flight mass spectrometry (MALDI-TOF MS) protein profiling. Sand fly occurrence and activity were evaluated based on surveyed locations, habitat requirements and climatic parameters. Moreover, a first comparison of European Ph. mascittii populations was made by two marker genes, cytochrome c oxidase subunit 1 (COI), and cytochrome b (cytb), as well as MALDI-TOF mass spectra. Our study provides new important records of Ph. mascittii in Austria and valuable data for prospective entomological surveys. MALDI-TOF MS protein profiling was shown to be a reliable tool for differentiation between sand fly species. Rising temperatures and globalization demand for regular entomological surveys to monitor changes in species distribution and composition. This is also important with respect to the possible vector competence of Ph. mascittii.